A fisher's perspective: Using half a century of local fisher knowledge to identify socio‐economic, ecological and legislative trends influencing angelshark (Squatina squatina) records in Wales - Francesca C. Mason; Jake Davies; Surshti Patel; Ben Wray; Charlie Bartlett; Michael Davies; Rowland Sharp; Carl Worrall; Jim Evans; John O'Connor; Sarah Davies; Alice Chamberlain; et al. (People and Nature)
Abstract The evolution of marine fisheries has broadly influenced the ecology, distribution and abundance of coastal elasmobranchs. However, quantifying these interactions remains a challenge due to the scarcity of historical records. Fishers' local ecological knowledge (LEK) is an essential tool in fisheries research, providing an avenue to regain scarce information on rare or cryptic species and contextualise modern observations and trends. LEK was collected from 27 semi‐structured interviews with commercial, recreational and charter fishers to better understand the ecology and temporal population trends for the Critically Endangered angelshark (Squatina squatina) within Wales, United Kingdom. Questions were designed to identify fisher perceptions of socio‐economic, ecological and legislative factors that drove changes in fishing effort for vessels operating within the ‘Welsh Zone’ between 1968 and 2019. Understanding how fleet‐wide spatiotemporal changes to fishing effort and capacity within commercial, recreational and charter fisheries have influenced historical records and sightings of S. squatina is an important consideration for assessing its status in Wales and designing appropriate actions to safeguard the species. Our findings identify structural changes to fisheries in Wales and key driving factors that likely decreased fishers' likelihood of encountering S. squatina over a 51‐year period. Therefore, we suggest recent published estimates of population declines may be overstated. Furthermore, we highlight the importance of quantifying and incorporating changes in fishing effort at a regional scale into future modelling approaches for elasmobranchs and advocate for the increased consideration of LEK in the development of management strategies. Read the free Plain Language Summary for this article on the Journal blog.